(3GdCTHGg hGdfXGFQ GdfMhjIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3eMeO Hf Lejd Hf jhSa GdQHGWj GdeGdcj s)
(3ChdgG (B:s
(3CeG HYO, aEf afhf GdYQHjI Ydi GNJdGa CfhGYgG gj Chd afhfj heHJOC GdCNHGQ cGf aj CMGOjKgG SeQj hTLhfj s
(3BNQgG (B:s
(3agj WGQFg Ydjg bWYkG, hJhLH LQ ZjQ GdefUQa LRekG cedJ GdCTHGg hGdfXGFQ GdfMhjI HMeO Gddg s
(3fSNI QGHYI JJab aj ChdgG eY Chd GdfSNI GdChdi JeGekGs
(3hcPdc aj BNQgG HGNJdGa jSjQ aj HYV GdCdaGXs
(3hHgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B22 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B100s
Keywords: (3GdfMhs